Naloxegol rescue with methylnaltrexone highly effective. Issue 3 (24th July 2020) - Brocklebank, Jenny; Miller, Elizabeth Jane; Fingas, Samuel
Abstract : Opioid-induced constipation (OIC) is common and can significantly affect quality of life. Naloxegol and methylnaltrexone are peripherally acting µ-opioid receptor antagonists (PAMORAs) which are effective for the management of OIC. We report on a case in the palliative care setting where a patient with established OIC had an inadequate response to naloxegol but an effective and immediate response to methylnaltrexone at the dose recommended for her weight. This is the first reported case of two PAMORAs used concomitantly.